Graphical methods for understanding changes in states: Understanding medication use pathways - Elizabeth A. Wise; Roy J. Adams; Constantine G. Lyketsos; Jeannie‐Marie Leoutsakos (International Journal of Methods in Psychiatric Research, 2022)
Abstract Objectives As epidemiological studies become longer and larger, the field needs novel graphical methods to visualize complex longitudinal data. The aim of this study was to present the Slinkyplot, a longitudinal crosstabulation, to illustrate patterns of antidepressant use in a large prospective cohort of older adults with mild cognitive impairment. Methods Data from the National Alzheimer's Coordinating Center are used to track switches between different states and types of antidepressant use. A Slinkyplot is populated with rows representing the state of medication use at each timepoint and columns representing the state at each subsequent visit. Results The constructed Slinkyplots display the common practice of switching on and off different antidepressants over time, with citalopram, sertraline, and bupropion most commonly used followed by switching to another SSRI or SNRI as second‐line treatment. Conclusions Slinkyplots are an innovative graphical means of visualizing complex patterns of transitions between different states over time for large longitudinal studies.